웹 크롤링과 기계학습 기법을 이용한 경영학 분야 KCI 저널의 주제어 분석 - 강경수(Kyung-Su Kang); 박세민(Se-Min Park) (대한경영학회지, 2019)
경영학은 이론, 실천, 과학, 기술 네 가지 측면을 지닌 종합학문으로 다양한 연구 대상을 선정하여 활발하게연구되고 있는 분야이다. 시대의 흐름에 따라 학문이 진부화되는 걸 방지하기 위해 새로운 연구주제 발견과다른 분야와 융복합하여 새로운 방향으로 발전을 도모하고 있다. 이에 새로운 연구 분야를 탐색하고 소멸하는과정을 빠르게 탐색하기 위해 주제어 분석을 시행하였다. 최근 인터넷의 등장과 대규모 비정형 데이터를 다루는개념과 기술이 급속도로 발전하면서 양질의 정보를 시간적·물리적 제약 없이 빠르게 도출할 수 있게 되었다. 본 연구에서는 2013년부터 2017년까지 5년간 KCI(Korea citation index) 등재지에 게재된 경영학 분야 논문을 웹 크롤러를 활용하여 총 8,185편의 논문을 수집하고, 데이터 클리닝 및 전처리 과정을 거쳐 4,210편에대한 논문의 주제어 분석하였다. 주제어는 두 가지로 방식으로 비교·분석하였다. 첫째, 말뭉치에서 작은 단위로나누는 토큰화 과정을 단일 명사로만 추출한 주제어 집합(a)과 저자들이 표현한 주제어 의미를 그대로 살린주제어 집합(b)으로 분류하였다. 둘째, 똑같은 뜻이지만 다양한 표현방식으로 분리된 단어를 유의어 사전을구축하여 한 단어로 통합하였다. 분석에 사용된 기법은 빈도 및 추세분석과 기계학습 기법인 연관규칙 분석과계층적 군집화를 사용하여 의미 있는 패턴을 발견하고자 하였다. 분석 결과, 빈도분석에서 5년간 활발하게 연구된 연구주제는 기업의 사회적 책임, 기업가정신, 고객 만족, 직무 만족, 신뢰 순으로 도출되었고, 추세분석에서 시간의 흐름에 따라 인사와 조직에 관한 연구에서 2016년부터 스타트업 주제어가 상승하였다. 연관규칙 분석은 지지도를 기준으로 결과를 도출하고 의미 있는 규칙을발견하였으며, 계층적 군집화에서 혁신과 창의성은 빅데이터와 관련된 것으로 도출되었다. 결과적으로 주제어집합(a)과 집합(b)을 비교·분석한 결과 상당한 차이가 존재하였다. 본 연구의 통해 개발된 웹 문서에서 자동으로 원하는 정보를 탐색하고 수집하는 웹 크롤러, 언어를 다루는자연어 처리 그리고 기계학습 기법을 적용하면 유의미한 결과를 짧은 시간 내에 도출할 수 있을 것으로 판단된다. 그리고 향후 경영학 분야의 연구 동향과 패턴을 발견하는데 이론적, 실무적 시사점을 제공하고 웹 크롤러와기계학습 기법이 경영학 분야에 활발히 적용될 수 있을 것으로 기대된다. Business administration is a comprehensive study with four aspects of theory, practice, science, and technology, and various research subjects have selected and actively studied. However, in order to prevent the obsolescence of learning over time, we tried to develop into a new direction by combining with other fields. Therefore, we analyzed the keywords to quickly search for the process of exploring and disappearing new research fields. With the advent of the Internet and the rapid development of technologies and concepts that deal with unstructured data, it has become possible to derive high-quality information quickly. In this study, a total of 8,185 papers were collected by using a web crawler in the field of business administration published in KCI (Korea citation index) list for five years from 2013 to 2017, and 4,210 papers. The keywords were compared and analyzed in two ways. It has integrated the words that are the same meaning but separate in various expressions into one word by synonyms dictionary. Moreover, we have classified them into two sets. A set of keywords (a) was a tokenized word with the smallest unit of word separation, and a set of keywords (b) in which the meanings of the words of the authors expressed as they are. The techniques used in the analysis were to find meaningful patterns using frequency and trend analysis, machine learning methods such as association rules and hierarchical clustering. As a result of the analysis, the keywords that have actively researched for five years in the frequency analysis derived from corporate social responsibility, entrepreneurship, customer satisfaction, job satisfaction, and trust. In the trend analysis, from 2016, the start-up has risen. In the association rules, results were derived based on support and meaningful rules were found. In the hierarchical clustering, the big data was related to innovation and creativity. Consequentially, there was a significant difference between the result the keyword set (a) and (b). In this study, the web crawler that automatically searches and collects data from web documents, natural language processing of handling text data, and applied machine learning techniques are expected to be able to derive meaningful relationships in a short time. It is expected that the web crawler and machine learning techniques will be actively applied in the field of business administration by providing the theoretical and practical implications for finding research keywords trends and patterns in the field of business administration in the future. KCI Citation Count: 0